International Financial Statistics January 2002. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2002)
The IMF's principal statistical publication, International Financial Statistics (IFS) Online, is the standard source of international statistics on all aspects of international and domestic finance. For most countries, IFS Online reports data on balance of payments, international investment position, international liquidity, monetary and financial statistics, exchange rates, interest rates, prices, production, government accounts, national accounts, and population. Updated monthly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet